Pertimbangan Hakim dalam Perluasan Wasiat Wajibah di Luar Ketentuan Kompilasi Hukum Indonesia - Wikandaru Soni Puspantoro (Universitas Sebelas Maret, 2025)
This study analyzes judicial considerations in expanding the mandatory bequest (wasiat wajibah) beyond Article 209 of the Compilation of Islamic Law (KHI), which limits it to adoptive children or parents, through a case study of Religious Court Decision No. 375/Pdt.P/2023/PA.Gtlo, issued September 8, 2023, by Judge Drs. Syufudin Mohamad, MH. The ruling designates the deceased Yusuf Jantu bin Njdjulu Jantu's (died July 15, 2023) wife as primary heir, sibling descendants as substitutes, and Applicants 2 (Yeni Yantu), 7 (Olin Yantu), and 8 (Citra Dewi Kau) as recipients based on significant social-moral ties, verified by witness testimony under Article 173 KHI. The research addresses key issues: how judicial considerations influence wasiat wajibah application, the legal bases employed, and implications for legal certainty and justice in Islamic inheritance law.Using normative legal research with qualitative analysis, statute and case approaches, primary sources (court decision, KHI), and secondary literature, results show judges use flexible ijtihad to accommodate modern family dynamics and administrative asset management without disputes. Legal bases include Articles 174 and 209 KHI, Supreme Court Circular No. 03/2015, jurisprudence like No. 10K/Pdt/2016, and fiqh references such as Bughyatul Mustarsyidin, aligning with precedents (e.g., Nos. 368K/AG/1995, 489K/AG/2011, 2/Pdt.G/2011/PA-Kbj, 268/Pdt.P/2020/PA.Amb) handling religious pluralism and non-conventional ties, capped at one-third of assets. This expansion ensures justice Aristotelian distributive (proportional to contributions), Rawlsian (protecting disadvantaged without harming primaries), Al-Attas' 'adl (harmonious fitrah placement preventing zulm), and maqasid shariah (hifz al-mal and hifz al-nasl for welfare) fostering social harmony in pluralistic Indonesia. However, unclear criteria risk inconsistency and uncertainty, relating directly to the queried issues by highlighting progressive innovation alongside needs for KHI revisions (inclusive emotional/economic bonds), judicial training, public education, and digital verification to sustain procedural, distributive, and sharia justice.